The great hunt [compact disc, unabridged] - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 1991)
The monumental task of retrieving the lost Horn of Valere-- the legendary horn that will raise the dead heroes of the Ages-- rests on the shoulders of Rand al'Thor. Rand begins the long journey of discovery-- a journey that starts with The Great Hunt.